Aconine attenuates osteoclast-mediated bone resorption and ferroptosis to improve osteoporosis via inhibiting NF-κB signaling - Xue, Chunchun; Luo, Huan; Wang, Libo; Deng, Qing; Kui, Wenyun; Da, Weiwei; Chen, Lin; Liu, Shuang; Xue, Yongpeng; Yang, Jiafan; Li, Lingxing; Du, Wenlan; et al. (Frontiers in Endocrinology, 2023)
Osteoporosis (OP), a prevalent public health concern primarily caused by osteoclast-induced bone resorption, requires potential therapeutic interventions.Natural compounds show potential as therapeutics for postmenopausal OP. Emerging evidence from in vitro osteoclastogenesis assay suggests that aconine (AC) serves as an osteoclast differentiation regulator without causing cytotoxicity. However, the in vivo functions of AC in various OP models need clarification. To address this, we administered intraperitoneal injections of AC to ovariectomy (OVX)-induced OP mice for 8 weeks and found that AC effectively reversed the OP phenotype of OVX mice, leading to a reduction in vertebral bone loss and restoration of high bone turnover markers. Specifically, AC significantly suppressed osteoclastogenesis in vivo and in vitro by decreasing the expression of osteoclast-specific genes such as NFATc1, c-Fos, Cathepsin K, and Mmp9. Importantly, AC can regulate osteoclast ferroptosis by suppressing Gpx4 and upregulating Acsl4, which is achieved through inhibition of the phosphorylation of I-κB and p65 in the NF-κB signaling pathway. These findings suggest that AC is a potential therapeutic option for managing OP by suppressing NF-κB signaling-mediated osteoclast ferroptosis and formation.